Cosmological Dynamics of a Hybrid Chameleon Scenario - Kourosh Nozari; Narges Rashidi (Advances in High Energy Physics)
We consider a hybrid scalar field which is nonminimally coupled to the matter and models a chameleon cosmology. By introducing an effective potential, we study the dependence of the effective potential's minimum and hybrid chameleon field's masses on the local matter density. In a dynamical system technique, we analyze the phase space of this two-field chameleon model, find its fixed points and study their stability. We show that the hybrid chameleon domination solution is a stable attractor and the universe in this setup experiences a phantom divide crossing.